2008
DOI: 10.2139/ssrn.1142728
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic Distributional Effects of Decoupled Payments: Single Farm Payments in the European Union

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 29 publications
2
51
0
Order By: Relevance
“…To illustrate the SPS capitalization, we use the model of Ciaian and Swinnen (2006) and Ciaian, Kancs, and Swinnen (2008). Agricultural goods are produced by two types of farms, 4 which permit the SPS variation across farms to be accounted for.…”
Section: Factors Influencing the Sps Capitalization Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…To illustrate the SPS capitalization, we use the model of Ciaian and Swinnen (2006) and Ciaian, Kancs, and Swinnen (2008). Agricultural goods are produced by two types of farms, 4 which permit the SPS variation across farms to be accounted for.…”
Section: Factors Influencing the Sps Capitalization Levelmentioning
confidence: 99%
“…According to Courleux et al (2008), Kilian and Salhofer (2008), and Ciaian, Kancs, and Swinnen (2008), the capitalization rate of the SPS largely depends on the ratio of the eligible area to the total number of entitlements. In the case of deficit entitlements relative to the eligible area the SPS benefits farms, it is not capitalized into land values.…”
Section: Land Entitlementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conceptual framework used in this paper is based on Ciaian, Kancs, and Swinnen (2008), Courleux et al (2008), and Kilian and Salhofer (2008).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The main instrument of CAP is subsidies. Subsidy payments may induce structural changes in the economy, such as productivity growth and exit/entry of farms (Ciaian et al, 2008).Various studies have shown that these CAP subsidies impact on the farm sector productivity. Some theoretical studies suggest that subsidies may have a positive or negative impact on farm production (Rizov et al, 2013) and productivity (Ackrill, 2008).…”
Section: Introductionmentioning
confidence: 99%